Strategi Pengembangan Wisata Lewu Bue Upaya Merangsang Pertumbuhan Pariwisata di Kecamatan Bukit Batu, Palangka Raya - Gojali, Muhammad; Rizali, Rizali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This research analyzes the potential of Lewu Bue Tourism in Bukit Batu District, Palangka Raya City, focusing on its strengths, weaknesses, opportunities, and threats. A quantitative descriptive approach was employed, with data collection through direct observation, interviews, field documentation, and questionnaires. Purposive sampling method was used to select research samples. SWOT analysis was employed to assess the internal and external factors influencing Lewu Bue Tourism. The results indicate that Lewu Bue Tourism possesses strengths and opportunities that can be leveraged for further development. The recommended development strategy is the SO strategy, utilizing existing strengths to optimize available opportunities. To stimulate tourism growth in Bukit Batu District through the development of Lewu Bue Tourism, several policies are recommended, including enhancing tourism attractions, utilizing digital technology, setting competitive and affordable prices, and marketing the affordability advantage through digital media. With the implementation of appropriate development strategies, Lewu Bue Tourism can become a competitive and sustainable tourist destination.